Penulisan Naskah Video Feature “Suara Dari Unpad: Jejak Calung Jinjing” Berbasis Struktur Tiga Babak (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2025)
Traditional arts as part of cultural heritage face significant challenges in maintaining their relevance amid social and cultural changes. One example is Calung Jinjing, a Sundanese bamboo-based performing art that originated from the creative process of students at Universitas Padjadjaran and later developed into a cultural reference within the wider community. This study examines the implementation of the Three-Act Structure in the scriptwriting process of the feature video “Suara dari Unpad: Jejak Calung Jinjing” as a strategy for conveying cultural messages effectively. The research aims to explain how the Three-Act Structure is applied to organize narrative flow, build emotional engagement, and strengthen the delivery of cultural meanings within a feature video format. This study employs a qualitative descriptive approach based on creative practice, supported by field research, observations, interviews with key cultural figures, and analysis of archival materials related to the history and development of Calung Jinjing. The findings indicate that the application of the Three-Act Structure—consisting of the beginning, middle, and ending acts—enables the scriptwriter to construct a coherent and communicative narrative that integrates historical context, cultural dynamics, and contemporary relevance. The structure helps transform research data into a compelling storyline while maintaining factual accuracy and cultural authenticity. This study implies that the Three-Act Structure can serve as an effective narrative framework for scriptwriting in cultural feature videos, particularly in presenting traditional arts as living social phenomena. Furthermore, the findings highlight the strategic role of scriptwriters in bridging cultural heritage and modern audiovisual storytelling.